An approach to model shaft voltage of wound rotor synchronous machines - Darques, K.; Tounzi, A.; Le Menach, Y.; Beddek, K.; Biet-Evrard, M. (2016 IEEE Conference on Electromagnetic Field Computation (CEFC), 2016)
In the case of high power synchronous machines, shaft voltage can induce high currents yielding to bearing damages but it can also constitutes a variable to be used to diagnosis some machine defects. Therefore, it is important to well model the phenomenon in order to use it in further diagnosis tool.